How is maternal employment associated with infant and young child feeding in Bangladesh? A systematic literature review and meta-analysis - M. A. Rifat; Plabon Sarkar; Israth Jahan Rimu; Syeda Saima Alam; Tasnu Ara; Tobias Lindström Battle; Manzur Kader; Sanjib Saha (PLoS ONE, 2025)
Background In the last three decades, the increasing trend in female employment in Bangladesh has been critically analyzed from a socioeconomic point of view; however, its impact on infant and young child feeding (IYCF) practices has yet to be systematically reviewed. The aim of this systematic review and meta-analysis is to investigate the association between these variables. Methods A systematic literature search was conducted in PubMed, Medline, Web of Science, Embase, CINAHL, and Google Scholar to retrieve relevant records with no restriction of publication period. The Covidence tool was used for screening and data extraction. Meta-analysis was carried out using random effect models. The Newcastle-Ottawa scale was used for the quality assessment of the included articles. Results A total of 24 articles were included. Of these, 16 focused on breastfeeding-related indicators, 6 focused on complementary feeding-related indicators, and 2 focused on both. Maternal employment was found to have both positive (protective) and negative (detrimental) associations with exclusive breastfeeding, whereas it was mainly positively associated with complementary feeding practices. Meta-analysis showed the pooled odds ratio of recommended early initiation of breastfeeding, exclusive breastfeeding, and complementary feeding among employed mothers were 0.79 (95% CI: 0.49, 1.27; p = 0.33), 0.32 (95% CI:0.16, 0.67; p = 0.002), and 1.07 (95% CI: 0.81, 1.42; p = 0.63) compared to their counterparts, respectively. Conclusions Maternal employment appears not to be a protective factor for some important breastfeeding indicators in Bangladesh. For example, there was a statistically significant lower likelihood of exclusive breastfeeding practice among employed mothers as compared to those who were not employed. Therefore, these issues should be taken into consideration when formulating relevant policies and interventions, e.g., breastfeeding-friendly workplace.